Economic valuation of gillnet fishing in Vembanad Lake, Kerala, South India, using market price approach - V. Chandrasekar; Nikita Gopal; V. Geethalakshmi; A. K. Mohanty; A. Vidhyavathi; M. Thilagavathi (Indian Journal of Fisheries, 2022)
Gillnet is the most widely followed selective and passive fishing gear system in all water bodies, especially in the traditionalfishing sector. Many past studies on gillnet fishing in the Vembanad Lake, Kerala, South India focussed on speciesavailability and gear-wise catch of major fishes and showed that there was a significant reduction in the fish catch.Thepresent study used market-based valuation method to estimate economic value generated through gillnet fishing operationin selected village panchayats spreading across three districts viz., Ernakulum, Alappuzha and Kottayam, bordering theVembanad Lake, during the period in 2019-20. The species-wise quantity and value of finfishes and shellfishes caught inthe gillnets from Vembanad Lake, in the three districts were analysed during the survey period. The total number of gillnetfishers living around the Vembanad Lake is about 6157 and the catch was estimated at 4645.97 t of both finfish and shellfishspecies, out of which shrimps formed around 72%. The maximum quantity of catch was observed for catfishes (Arius spp.)at 278.6 t per annum, which fetched a value ₹4.46 crores, followed by Etroplus maculatus at 149 t (₹3.58 crores in valueterms). The economic value generated through gillnet fishing is estimated at ₹57.94 crores.Keywords: Economic value, Gillnet fishing, Market price method, Vembanad Lake